Learning Technical Vocabulary through a Mobile App: English Language Teachers’ Perspectives - Zuraina, Ali (Universiti Malaysia Pahang, 2016)
Mobile learning or m-learning is essential for a wide range of learning opportunities. Using mobile app such as in the use of VocBlast, which contains ten (10) interesting games enables students at tertiary level to enhance and enrich their technical vocabulary. The specific objective of this study was to examine English language teachers’ views concerning the use of VocBlast in assisting students in Universiti Malaysia Pahang to learn technical vocabulary. This study employed a qualitative approach involving four language teachers as its samples. They were interviewed via e-mails, where the questions were uploaded in Google Docs. The interview data were analyzed thematically, and generated four (4) themes; hints given are useful for students, VocBlast enlivens students’ learning, VocBlast can serve as a supplementary learning material and VocBlast can act as indirect vocabulary learning tool. An implication of this is the possibility of integrating m-learning into teaching-learning pedagogy especially at tertiary level.